A review on available resistant varieties and the biotechnology application to reduce the impact of sheath blight disease on rice (Oryza sativa L.) / Nur Farhanah Azlan - Azlan, Nur Farhanah (Faculty of Plantation and Agrotechnology, 2018)
Sheath blight disease, caused by the fungus Rhizoctonia solani Kuhn, is one of the most destructive diseases (Oryza sativa L.) that causing substantial yield loss in rice. Yield losses caused by this disease represent a major threat to fulfill the future rice demand. Sheath blight is a rice fungal disease which can has caused yield loss up to 50% of rice production. Therefore, in order to eradicate this problem, various methods have been applied, including the introduction of biotechnology to produce new varieties that are more resistant to the sheath blight disease. Hence, the application of marker assisted selection, genetic engineering, backcross breeding, mapping of QTLs, application of PCR, Agrobacterium-mediated transformation and Bulk Segregant Analysis (BSA) are several biotechnology applications that being applied in developing susceptible varities to become new varirt that is resistance to sheath blight. There are several varieties developed from adoption of biotechnology that are resistant to sheath blight disease such as improved Pusa Basmati 1, Taipei 309 (TPC1), 32R x Nipponbare, rice line WSS2, rice line ARC10531 x BPT-5204, UMKRC9 and Sahbhagi Dhan.